Beta Thalassemia - Zakaria, Marwa; Hassan, Tamer; Zakaria, Marwa; Hassan, Tamer (IntechOpen, 2020)
Beta thalassemia is a common blood disorder worldwide. Thousands of infants with beta thalassemia are born each year. This book covers most of the aspects related to this disease and greatly helps in understanding this disease and its complications. Of interest are clinical studies as well as basic and translational research reports regarding pathogenesis, genetics, diagnosis as well as standard and novel therapies. This book intends to provide the reader with a comprehensive overview of today$1 (Bs practices and tomorrow$1 (Bs possibilities about beta thalassemia.s
English
Keywords: Haematology; Haematology